2013
DOI: 10.1016/j.toxlet.2012.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-induced oxidative DNA damage in neuronal SH-SY5Y cells: Attenuation of thymine base lesions by glutathione and N-acetylcysteine

Abstract: Manganese (Mn) is an essential trace element required for normal function and development. However, exposure to this metal at elevated levels may cause manganism, a progressive neurodegenerative disorder with neurological symptoms similar to idiopathic Parkinson’s disease (IPD). Elevated body burdens of Mn from exposure to parental nutrition, vapors in mines and smelters and welding fumes have been associated with neurological health concerns. The underlying mechanism of Mn neurotoxicity remains unclear. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 38 publications
2
63
0
Order By: Relevance
“…ROS formation is also thought to be the cause of the pro-apoptotic effect of Cu on neurons (Chen et al, 2009) and its pro-necrotic effect in astrocytes (Scheiber et al, 2010) at concentrations seen in pus in the present study. Formation of ROS may also be stimulated by Mn (Stephenson et al, 2013) and Cr (Bagchi et al, 2002;Davidson et al, 2007) at low micromolar concentration, but the concentration of these ions in pus in the present study was submicromolar, so it is difficult to evaluate their importance for symptom generation in our patients.…”
Section: Elevated Levels Of Ca and Trace Metals In Brain Abscesses Anmentioning
confidence: 70%
“…ROS formation is also thought to be the cause of the pro-apoptotic effect of Cu on neurons (Chen et al, 2009) and its pro-necrotic effect in astrocytes (Scheiber et al, 2010) at concentrations seen in pus in the present study. Formation of ROS may also be stimulated by Mn (Stephenson et al, 2013) and Cr (Bagchi et al, 2002;Davidson et al, 2007) at low micromolar concentration, but the concentration of these ions in pus in the present study was submicromolar, so it is difficult to evaluate their importance for symptom generation in our patients.…”
Section: Elevated Levels Of Ca and Trace Metals In Brain Abscesses Anmentioning
confidence: 70%
“…5E and G). Oxidative stress has been implicated in Mn neurotoxicity (Milatovic et al, 2009;Herná ndez et al, 2011;Stephenson et al, 2013), and it has been reported that Mn induces production of H 2 O 2 in vitro (Posser et al, 2009) and hydroxyl radical in vivo (Bałasz et al, 2015). This result demonstrates that the hippocampus is susceptible to oxidative stress induced by perinatal Mn exposure and the effects of excessive levels of Mn in this region have consequences for the antioxidant defense system in rats that last into adulthood (PND70).…”
Section: Discussionmentioning
confidence: 90%
“…15 Exposure of neuroblastoma SH-SY5Y cells to low, subcytotoxic, MnCl 2 concentrations (2 mM) resulted in an eight-fold increase in DNA damage. 20 In human leukocytes, Mn exposure did not increase the amount of strand breaks or cross-links. 21 Potassium permanganate has been shown to cause DNA strand breaks in human peripheral blood lymphocytes.…”
Section: Damage Induced By Manganese At the Dna Levelmentioning
confidence: 91%